Integrating Islam: political and religious challenges in contemporary France - Laurence, Jonathan (Brookings Institution Press, 2006)
"Portrays the more complex reality of Muslim integration into French politics and society. Special attention devoted to the policies developed by successive French governments to encourage integration and discourage extremism"--Provided by publisher